Pengembangan Media Pembelajaran Mobile Learning dengan Fitur Gamifikasi pada Materi Kebutuhan dalam Mata Pelajaran IPS - Musthofa, Danis Nurul; Cahyono, Arie Eko; Ulfa, Noviana Mariatul (Universitas Nusantara PGRI Kediri, 2025)
This study aims to develop mobile learning-based educational media, specifically on the topic of needs within the subject of Social Sciences (IPS) at SMP Negeri 8 Jember. By utilizing advancements in information and communication technology, this research adopts the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The results indicate that the developed mobile learning application, named